A case study of a strategic initiative in pediatric rehabilitation transition services: An insiders' perspective on team principles and practices - King, Gillian; Bowman, Laura R.; Curran, C. J.; Oh, Anna; Thompson, Laura; McDougall, Carolyn; Menna-Dack, Dolly; Howson-Strong, Laura (Frontiers in Rehabilitation Sciences, 2022)
Aims: The aim was to describe an innovative initiative that took place in a pediatric rehabilitation hospital. The goal of this organization-wide strategic initiative, called the Transition Strategy, was to improve service delivery to children/youth with disabilities and their families at times of transition. The research question was: What are the key elements that have contributed to the success of the Strategy, from the perspective of team members? The objectives were to describe: (a) the guiding principles underlying team functioning and team practices, (b) key enablers of positive team functioning, (c) the nature of effective team practices, and (d) lessons learned. Methods: A holistic descriptive case study was conducted, utilizing historical documents, tracked outcome data, and the experiences and insights of multidisciplinary team members (the authors). Reflecting an insiders’ perspective, the impressions of team members were key sources of data. The perspectives of team members were used to generate key teamwork principles, enablers of team functioning, team practices, and key learnings. Findings and Discussion: Team members identified four guiding humanistic principles (respect, support, partnership, and open communication). These principles underpinned three novel practices that contributed to team effectiveness in the eyes of team members: supportive relational practices, human-centered co-design, and solution-focused communication. Key enablers were the relational style of leadership, and a team climate of innovation, autonomy, and trust, supported by the organizational vision. This team climate fostered a sense of psychological safety, thereby encouraging both experimentation and learning from failure. Conclusions: This article provides information for other healthcare organizations interested in understanding the Strategy’s value and its implementation. It provides a practical example of how to adopt a humanistic approach to health care, leading to both innovative service development and thriving among team members.